Fast ortho-to-para conversion of molecular hydrogen in chemisorption and matrix-isolation systems - Ueta, Hirokazu; Fukutani, Katsuyuki; Yamakawa, Koichiro (Frontiers in Chemistry, 2023)
Molecular hydrogen has two nuclear-spin modifications called ortho and para. Because of the symmetry restriction with respect to permutation of the two protons, the ortho and para isomers take only odd and even values of the rotational quantum number, respectively. The ortho-to-para conversion is promoted in condensed systems, to which the excess rotational energy and spin angular momentum are transferred. We review recent studies on fast ortho-to-para conversion of hydrogen in molecular chemisorption and matrix isolation systems, discussing the conversion mechanism as well as rotational-relaxation pathways.